Girinos de espécies de Hyla do grupo "Albosignata" (Amphibia, Anura, Hylidae) - Gomes, Márcia dos Reis (1996)
Tadpoles of the five Hyla species belonging to the "albosignata" group were studied and illustrated, and their shared characters used to define the group. Tadpoles of the "albosignata" group were shown to be associated with mountain streams from 800m to higher elevation. Two groups of tadpoles have been distinguished, the first involving H. albosignata and H. cavicola and the second H. callipygia, H. fluminea, and H. leucopygia. A key to the tadpoles of the group was elaborated taking into consideration color pattern, oral features and some other morphological traits. Some remarks on ecological aspects and environmental prefferences were made, associating some of them as a wider reproductive period and lower altitude streams occupation with the first group of tadpoles. It was observed that the tadpoles of the "albosignata" group get to their maximum size by stage 38, and that the green collor typical of all adults appears at different developmental stages and on different body parts depending on the species considered. Among the five species of the group it was found that H. cavicola shows the green color at the earliest stage (36) and H. albosignata at the later (41). The known geographic range for H. callipygia, H. cavicola, and H. fluminea was extended.